Genetic relationships of Phragmipedium species (Orchidacea)using amplified fragment lenght polymorphism (AFLP) analysis - Rodríguez Salas, Manuel (2007)
The objective of this study is to evaluate the genetic relationships of eight Peruvian species of the genus Phragmipedium using amplified fragment length polymorphisms and a phenetic analysis (UPGMA). The analysis showed that the species are phenetically grouped in four large clusters. The first cluster includes species from the Himantopetalum (P. pearcei and P. richteri) and Lorifolia (P. boissierianum) sections. The second cluster comprised the species of the Micropetalum section (P. besseae and P. schlimii). The third one included P. kovachii in the Schluckebieria section. The fourth cluster contains species of the Phragmipedium (P. caudatum and P. wallisii) section. The results show that AFLP analysis is a powerful genetic tool for the analysis of the taxonomy of orchids from the diverse and complex Phragmipedium genus.